2014
DOI: 10.5935/abc.20140096
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Embolic Potential of Cardiac Tumors

Abstract: BackgroundCardiac tumors are rare, mostly benign with high embolic potential.ObjectivesTo correlate the histological type of cardiac masses with their embolic potential, implantation site and long term follow up in patients undergoing surgery.MethodsBetween January 1986 and December 2011, we retrospectively analyzed 185 consecutive patients who underwent excision of intracardiac mass (119 females, mean age 48±20 years). In 145 patients, the left atrium was the origin site. 72% were asymptomatic and prior embol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 12 publications
0
22
0
10
Order By: Relevance
“…Achados menos frequentes são a leucocitose, a trombocitopenia, a cianose, o baqueteamento digital e o fenómeno de Raynaud. Os sintomas sistémicos remitem após excisão tumoral 5,6,8 . Ao exame físico, mais de metade dos doentes podem apresentar sopros sistólicos ou diastólicos, dependendo do tamanho, localização e mobilidade do mixoma, assim como da posição do doente.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Achados menos frequentes são a leucocitose, a trombocitopenia, a cianose, o baqueteamento digital e o fenómeno de Raynaud. Os sintomas sistémicos remitem após excisão tumoral 5,6,8 . Ao exame físico, mais de metade dos doentes podem apresentar sopros sistólicos ou diastólicos, dependendo do tamanho, localização e mobilidade do mixoma, assim como da posição do doente.…”
Section: Discussionunclassified
“…A tomografia axial computorizada, ressonância magnética e, por vezes, a angiografia coronária, podem complementar o estudo diagnóstico e contribuir para a planificação da estratégia terapêutica. O diagnóstico definitivo é realizado após excisão tumoral e avaliação anátomo-patológica, apoiada pela avaliação imuno-histoquímica [5][6][7][8] . O tratamento de eleição dos mixomas cardíacos é a excisão cirúrgica, sendo geralmente curativa.…”
Section: Galicia Clin 2015; 76 (2) : 74-76unclassified
“…were found to be associated with a higher risk of embolic events in the univariate analysis. Dias et al 16 reported that the tumor size, atrial fibrillation, and valve impairment were not associated with the embolic events. On the other hand, Liang et al showed that patients who developed embolic events had significantly larger cardiac myxomas and left atrial diameters.…”
Section: Ta B L E 1 Comparison Of Demographic and Laboratory Parametementioning
confidence: 99%
“…Systemic embolisation occurs in around 30% of cases either from tumour fragmentation or complete tumour detachment. Cerebral embolism is the most common site followed by coronary, renal, mesenteric and peripheral arteries 2. Embolisation of cardiac myxoma to peripheral arteries leading to acute limb ischaemia has rarely been reported before 3.…”
Section: Descriptionmentioning
confidence: 99%